Burger's Medicinal Chemistry and Drug Discovery 2010
DOI: 10.1002/0471266949.bmc166
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Survey of Albumin Drug Interaction and Preliminary Applications in Cancer Chemotherapy

Abstract: An overview of the results of a comprehensive crystallographic structural survey of drug binding to human albumin at atomic resolution is presented. More than 350 complexes were examined, ultimately producing more than 200 structures with representatives in every major therapeutic category. The survey indicated 12 independent drug‐binding locations dominated by the three sites located within subdomains IIA, IIIA, and IB. Site IB, the most structurally accommodating site on albumin, revealed a propensity for la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 21 publications
5
44
0
Order By: Relevance
“…A binding pocket in the subdomain IB has recently been recognized as a secondary binding site for some other compounds with different properties such as indomethacin, iophenoxic acid, naproxen, myristic acid, warfarin, lidocaine, and bilirubin [29]. Because of this finding, it has been proposed that subdomain IB could be a third drug-binding region of HSA [51,52] and therefore the ‘Three-Site Model’ for drug-binding regions of HSA was proposed [29]. In a recent study, Wang et al investigated the albumin-binding interactions with anticancer cytotoxic drugs such as camptothecin, etoposide, teniposide, bicalutamide, and idarubicin at the scale of atomic details [32].…”
Section: Albumin Types Structures and Binding Sitesmentioning
confidence: 99%
“…A binding pocket in the subdomain IB has recently been recognized as a secondary binding site for some other compounds with different properties such as indomethacin, iophenoxic acid, naproxen, myristic acid, warfarin, lidocaine, and bilirubin [29]. Because of this finding, it has been proposed that subdomain IB could be a third drug-binding region of HSA [51,52] and therefore the ‘Three-Site Model’ for drug-binding regions of HSA was proposed [29]. In a recent study, Wang et al investigated the albumin-binding interactions with anticancer cytotoxic drugs such as camptothecin, etoposide, teniposide, bicalutamide, and idarubicin at the scale of atomic details [32].…”
Section: Albumin Types Structures and Binding Sitesmentioning
confidence: 99%
“…Crystallographic analysis of cancer drugs binding to albumin demonstrates that they preferably bind DIB, rather than Drug sites 1 and 2 [45], and DIB is now considered Drug site 3 [50]. Interestingly, in a recent study where more than 200 atomic structures of human albumin in complex with various pharmaceuticals and endogenous ligands were analysed, small hydrophobic and anionic drugs showed preference for Drug sites 1 and 2, while complex heterocyclic ligands preferred Drug site 3 [51]. As ligands and drugs may compete for the same binding sites on albumin, their effect will depend on the presence of competitors, which results in their free fractions relative to the albumin-bound.…”
Section: Albumin -A Multifunctional Transportermentioning
confidence: 99%
“…13 Sudlow found two primary drug-binding sites on the protein, named Sudlow sites I and II. 14,15 The first crystallographic structure of HSA showed that HSA is a heart-shaped protein, which is composed of 585 amino acid residues with three structurally homologous domains (I, II, and III).…”
Section: * S Supporting Informationmentioning
confidence: 99%